Analysis of Nurses' Compliance with Patient Safety in the Inpatient Room of RSI Malahayati Medan - Zendrato, Bryan Ifolala; Theo, Deli; Fitriani, Arifah Devi (PROMOTOR, 2025)
A patient safety program is a system that ensures hospitals make care or health services for patients safer. Patient safety is concerned with patient care, incidents that can be avoided or should not occur and have been considered a discipline. However, it must be admitted that in these quality services there are still shortcomings in patient services, especially related to patient safety incidents. The purpose of the study was to analyze the factors that affect nurses' compliance with patient safety in the inpatient room at RSI Malahayati Medan. The research design used in this study is an analytical survey with a cross sectional design. The population in this study is all inpatient room nurses at Malahayati Hospital Medan. The number of nurses in the inpatient room is 45 people. The number of samples to be studied is 45 people. Data analysis was carried out by univariate, bivariate and multivariate analysis. The arial tests used are chi square and ariable regression tests. The results of the chi square test research show that there is an influence of 7 variables, namely leadership, rewards. Structure, job design, age, tenure and education have a p-value <α 0.05, meaning leadership, rewards. Structure, job design, age, working period and education affect nurse compliance at RSI Malahayati Medan and the multivariate test has 7 variables affecting leadership, rewards. Structure, job design, age, working period and education with the results of the multiple variable regression test showed that the most dominant ariable-reward with an odds ratio (OR) of 6,916 means 6 times affecting nurses' compliance with patient safety. It was concluded that the reward variable had the most influence on nurses' compliance with patient safety at RSI Malahayati Medan. It is recommended for the hospital to build more positive leadership for the employee environment, facilitate employees to continue learning, pay attention to a good organizational structure, decompose employee duties and especially pay attention to income, incentives and bonuses for employees.